MANAJEMEN EKSTRAKURIKULER DALAM MEWUJUDKAN PRESTASI NON AKADEMIK DI SMA NEGERI 1 MENGANTI GRESIK: Penelitian Deskriptif - Moh Wahyu Nurcahyo; Ainur Rifqi; Karwanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe and analyze the management of extracurricular activities at SMA Negeri 1 Menganti Gresik as an effort to develop students’ character and non-academic skills. Using a qualitative approach with a case study method, data were collected through in-depth interviews, observation, and documentation. The findings reveal that extracurricular management at the school is well-organized and structured, covering program planning, implementation, evaluation, and transparent financial management. Extracurricular activities such as futsal, hockey, scouting, and student organizations have significantly contributed to the improvement of academic achievement, self-confidence, leadership, and social skills among students. The main challenges include limited resources and low student participation, which are addressed through program innovation, collaboration with external parties, and the involvement of parents and alumni. This study confirms that extracurricular activities are not merely complementary to education but are an integral component in shaping holistically excellent students. The findings are expected to serve as a reference for other schools in managing extracurricular programs effectively and for policymakers to strengthen the role of extracurricular activities within the national education system